The Role of Akhlaq Teachers in Shaping Student Character: Peran Guru Akidah Akhlaq dalam Membentuk Karakter Siswa - Irsyad, Habib Muhammad; Salim, Hakimmudin (Indonesian Journal of Innovation Studies, 2025)
General Background: Character education plays a fundamental role in shaping the moral quality of students and is central to the goals of Islamic education. Specific Background: In the context of Madrasah Tsanawiyah (MTs), Akidah Akhlak teachers serve as moral agents who internalize religious and ethical values into students’ behavior. Knowledge Gap: However, limited empirical studies have examined the strategic role of these teachers in shaping character within Indonesia’s formal education system. Aims: This study aims to explore the specific roles, challenges, and solutions implemented by Akidah Akhlak teachers in forming student character at MTs Negeri 7 Klaten. Results: Using a qualitative case study through interviews, observations, and documentation, the research found that teachers play multifaceted roles—educator, role model, and moral guide—using strategies like habituation, religious practices, and collaboration with counselors and parents. Novelty: The integration of Islamic moral instruction with contextual character education aligned with national and global values presents a unique model of character formation. Implications: The findings suggest that synergizing religious pedagogy with collaborative educational ecosystems enhances the effectiveness of character building, offering insights for broader applications in faith-based education institutions.Highlight : The Akidah Akhlak teacher plays a key role in shaping student character through modeling, spiritual motivation, and discipline. Character formation is most effective when involving collaboration between teachers, BK counselors, and parents. Modern challenges such as social media and weak communication hinder moral education and require contextual religious guidance. Keywords : Role of Teacher, Character Education, Islamic Morality, Student Behavior, Moral Development